Predictive Model for Response Rate to Narrowband Ultraviolet B Phototherapy in Vitiligo: A Retrospective Cohort Study of 579 Patients - Raúl Cabrera; Lia Hojman; Francisca Recule; Rodrigo Sepulveda; Iris Delgado (Medical Journals Sweden, 2018)
Vitiligo is an acquired depigmenting disorder. To date, there is no predictive model for its response rate to narrowband ultraviolet B (NBUVB) phototherapy. The aim of this study was to investigate the different types of response of patients with non-segmental vitiligo undergoing NBUVB 3 times a week. Many patients who were previously considered non-responders were given the opportunity to continue the treatment. Long-term maintenance of treatment and follow-up of a cohort of 579 patients enabled different subtypes of response (very rapid, rapid, average, slow and "non-responders") to be described for the first time, and a predictive model of response to be constructed based on repigmentation rate in the first 48 sessions of NBUVB. Among those patients who did not respond during the first 48 sessions, a new subgroup of patients was found, termed "very-slow" responders, who achieved a low, but significant, level of repigmentation after 96 sessions of NBUVB.